The association between sarcopenia and bladder cancer-specific mortality and all-cause mortality after radical cystectomy: A systematic review and meta-analysis. Issue 1 (2nd January 2021) - Ibilibor, Christine; Psutka, Sarah P.; Herrera, Jesus; Rivero, J. Ricardo; Wang, Hanzhang; Farrell, Ann M.; Liss, Michael A.; Pruthi, Deepak; Mansour, Ahmed M.; Svatek, Robert; Kaushik, Dharam
ABSTRACT: Objective : To compare cancer-specific mortality (CSM) and all-cause mortality (ACM) between patients with and without sarcopenia who underwent radical cystectomy for bladder cancer. Materials and methods : We performed a systematic review and meta-analysis of original articles published from October 2010 to March 2019 evaluating the effect of sarcopenia on CSM and ACM. We extracted hazard ratios (HRs) and 95% confidence intervals (CIs) for CSM and ACM from the included studies. Heterogeneity amongst studies was measured using the Q -statistic and the I 2 index. Meta-analysis was performed using a random-effects model if heterogeneity was high and fixed-effects models if heterogeneity was low. Results : We identified 145 publications, of which five were included in the meta-analysis. These five studies represented 1447 patients of which 453 were classified as sarcopenic and 534 were non-sarcopenic. CSM and ACM were increased in sarcopenic vs non-sarcopenic patients (HR 1.64, 95% CI 1.30–2.08, P < 0.01 and HR 1.41, 95% CI 1.22–1.62, P < 0.01, respectively). Conclusions : Sarcopenia is significantly associated with increased CSM and ACM in bladder cancer. Identifying patients with sarcopenia will augment preoperative counselling and planning. Further studies are required to evaluate targeted interventions in patients with sarcopenia to improve clinical outcomes. Abbreviations: ACM: all-cause mortality; ASA: American Association of Anesthesiologists; BMI: body mass index; CCI: Charlson Comorbidity Index; CSM: cancer-specific mortality; CSS: cancer-specific survival; ECOG: Eastern Cooperative Oncology Group; HR: hazard ratio; NAC: neoadjuvant chemotherapy; NIH: National Institutes of Health; OS: overall survival; RC: radical cystectomy; RCT: randomised controlled trial; SMI: Skeletal Muscle Index